Production of cation vacancies in alkali halides by ionizing radiation; Soviet Physics Journal; Vol. 18, № 3 - Vorobyev А. А. Alexander Akimovich; Annenkov Yu. M.; Pichugin V. F. Vladimir Fyodorovich; Frangul'yan T. S.; Nesterenko A. P. (1975, 1975)
В фонде НТБ ТПУ отсутствует